Peningkatan Citra Dan Kepercayaan Masyarakat Pada Rumah Sakit Milik Pemerintah Melalui Perbaikan Sistem Penyampaian Jasa - Rahab Rahab; Alisa Tri Nawarini (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2012)
The aims of this research is to analyze: 1) the effect of physical support to contact personnel, 2) the effect of service delivery systems that consist of physical support and contact personnel to hospital image, 3) the effect of service delivery systems that consist of physical support and contact personnel to hospital consumer trust’, 4) the effect of hospital image to consumer trust’. This research is a quantitative research. This research is descriptive and verivicative research with descriptive and explanatory survey methods. Type of investigation in this research is causality with time coverage is cross sectional. Sampling method used in this research is multistage sampling by taking four public hospital in Banyumas residence with 100 hospital consumers’ as respondents (patients and their family). Data analysis methods used in this research are descriptive analysis and path analysis. The research results show that: 1) Physical support correlate to contact personnel, 2) physical support affecting hospital image, 3) contact personnel is not affecting hospital image, 4) physical support affecting consumers’ trust, 5) contact personnel affecting consumers’ trust, 6) hospital image affecting consumers’ trust.